2003
DOI: 10.1038/sj.bjc.6600793
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effects of butyrate and bile acids on apoptosis of human colon adenoma cells: differential activation of PKC and MAP kinases

Abstract: Butyrate, produced in the colon by fermentation of dietary fibre, induces apoptosis in colon adenoma and cancer cell lines, which may contribute to protection against colorectal cancer. However, butyrate is present in the colon along with other dietary factors, including unconjugated bile acids, which are tumour promoters. We have shown previously that the proapoptotic effects of butyrate on AA/C1 human adenoma cells were reduced in the presence of bile acids. To determine the cellular basis of this interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 37 publications
8
38
2
Order By: Relevance
“…Resveratrol has been proposed not only as a cancer chemopreventive reagent, but also an adjuvant therapy in the treatment of cancer (Fukui et al, 2010). In previous studies, PKCα was considered as a PKC isoform which was associated with proliferation in many cell types, and many reports have indicated that the inhibition of PKCα was sufficient for apoptosis induction, suggesting that PKCα could suppress apoptosis in some cells (McMillan et al, 2003;\Wen-Sheng et al, 2006). We also found that PKCα was stimulated by resveratrol.…”
Section: Discussionsupporting
confidence: 55%
“…Resveratrol has been proposed not only as a cancer chemopreventive reagent, but also an adjuvant therapy in the treatment of cancer (Fukui et al, 2010). In previous studies, PKCα was considered as a PKC isoform which was associated with proliferation in many cell types, and many reports have indicated that the inhibition of PKCα was sufficient for apoptosis induction, suggesting that PKCα could suppress apoptosis in some cells (McMillan et al, 2003;\Wen-Sheng et al, 2006). We also found that PKCα was stimulated by resveratrol.…”
Section: Discussionsupporting
confidence: 55%
“…Interestingly, these findings, combined with previous evidence, indicate a cell typespecific regulation of PKC␦ gene expression in response to HDAC inhibition. For instance, in nasopharyngeal carcinoma and AA/C1 adenoma cells, HDAC inhibitors, such as TSA and NaBu, did not alter the PKC␦ expression levels but rather led to a distinct cellular sub-localization of the PKC␦ protein (92,93). By contrast, in human hepatoma Hep3B cells, TSA was found to specifically down-regulate PKC␦ levels (94).…”
Section: Discussionmentioning
confidence: 99%
“…In studies in colonic cells, PKC signaling pathways are also involved in cell cycle and cell death regulation (Goldstein et al, 1995;Qiao et al, 1996;Sauma et al, 1996;Abraham et al, 1998;Perletti et al, 1998Perletti et al, , 1999Andre et al, 1999;Assert et al, 1999;Weller et al, 1999;Umar et al, 2000;Cerda et al, 2001;Lin et al, 2002;McMillan et al, 2003;Di Mari et al, 2005;Meyer et al, 2005). Several studies, including our own investigations, have demonstrated a tumor suppressor role for PKC-d in colon cancer cells, including cell cycle arrest and enhanced apoptosis (Weller et al, 1999;Cerda et al, 2001;Lin et al, 2002;McMillan et al, 2003;Perletti et al, 2004Perletti et al, , 2005. There is, however, at least one report that inhibition of this isoenzyme is sufficient to promote cell death (Lewis et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Studies have demonstrated that PKC-d promotes cell death in many noncolonic cell lines, including keratinocytes (Denning et al, 1998), neutrophils (Pongracz et al, 1999), cerebral granule cells (Villalba, 1998), HL-60 and prostate cancer cells (Savickiene et al, 1999;Yin et al, 2005), but not in breast cancer cells (McCracken et al, 2003;Nabha et al, 2005). In studies in colonic cells, PKC signaling pathways are also involved in cell cycle and cell death regulation (Goldstein et al, 1995;Qiao et al, 1996;Sauma et al, 1996;Abraham et al, 1998;Perletti et al, 1998Perletti et al, , 1999Andre et al, 1999;Assert et al, 1999;Weller et al, 1999;Umar et al, 2000;Cerda et al, 2001;Lin et al, 2002;McMillan et al, 2003;Di Mari et al, 2005;Meyer et al, 2005). Several studies, including our own investigations, have demonstrated a tumor suppressor role for PKC-d in colon cancer cells, including cell cycle arrest and enhanced apoptosis (Weller et al, 1999;Cerda et al, 2001;Lin et al, 2002;McMillan et al, 2003;Perletti et al, 2004Perletti et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%